Tuning transition temperature of magnetocaloric Mn1.8Fe0.2(P0.59Si0.41)x alloys for cryogenic magnetic refrigeration. (1st July 2020) - Lai, Jiawei; Tang, Xin; Sepehri-Amin, H.; Hono, K.
Abstract: Giant magnetocaloric effect in Mn1.8 Fe0.2 (P0.59 Si0.41 ) x (  x   =  1.00, 1.01,  1.02,  1.03,  1.04) alloys is assessed for cryogenic temperature applications. We found that the Curie temperature can be tuned from. 300 K to 99 K by increase of Mn/Fe and P/Si ratios. We systematically optimized metal/non-metal ratio and homogenization condition to maximize the volume fraction of the Fe2 P-type phase. A giant isothermal magnetic entropy changes of 10.6 and 14.0 J/kgK under a magnetic field of 2.0 and 5.0 T is obtained at 117.0 K for Mn1.8 Fe0.2 (P0.59 Si0.41 )1.03 alloy. This work demonstrates low-cost Mn-Fe-P-Si alloys with giant MCE are competitive candidates compare to the rare-earth-containing magnetocaloric compounds for cryogenic applications. Graphical abstract: Image, graphical abstract